PENGEMBANGAN MODUL PRAKTIKUM BIOKIMIA: ANALISIS KANDUNGAN JAHE DENGAN GC-MS TERINTEGRASI PENDIDIKAN ISLAMI MENGGUNAKAN MODEL INKUIRI TERBIMBING - Wicaksono, Ardian Trio; Mubarak, Hafiz; Fatya, Alvian Ikhsanul; Ardiansyah, Ardiansyah (UIN AR-RANIRY, 2024)
This research aims to develop biochemistry practical instructions that are integrated with Islamic education based on local wisdom in South Kalimantan which utilizes Gas Chromatography-Mass Spectrometry (GC-MS) technology using a guided inquiry model. The method for developing practical instructions uses the ADDIE model including the needs analysis, design, development, implementation and evaluation stages. Data was obtained through interviews with Banjar residents, literature studies to integrate Islam and science, validity tests of material experts and media experts, as well as surveys of student responses to practical instructions that have been implemented in the learning environment. The research results showed that the development of guided inquiry-based practical instructions that utilized GC-MS technology was categorized as the learning source (78.75), and very valid as the instructional Media (81.25). Then, based on student responses, this practical guide received an excellent category (95) to be applied to the biochemistry practical course